2022
DOI: 10.1007/s12520-022-01505-6
|View full text |Cite
|
Sign up to set email alerts
|

Mithraism under the microscope: new revelations about rituals through micromorphology, histotaphonomy and zooarchaeology

Abstract: This paper is the first to use an innovative multi-proxy approach to obtain insights into hitherto unknown Mithraic cult practices. Using soil micromorphology, zooarchaeology and histotaphonomy, we investigated two mithraea (Biesheim FR, Kempraten CH) and one cult cave (Zillis CH). This was also the first study to include micromorphological and histotaphonomic approaches within the context of Mithraic research. The systematic evaluation of thermal alteration and bioerosion (in particular bacterial attack) on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The incidence of postoperative urinary tract infection varies depending on the population, study, and surgical approach, and patients may experience severe recurrence of postoperative urinary tract infection. Therefore, great attention should be paid to actively intervene to minimize the occurrence of urination and urination [ 27 , 28 ]. The results of this study showed that the incidence of urinary incontinence and voiding was 4% (2 cases) in the study group and 18% (9 cases) in the study group.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…The incidence of postoperative urinary tract infection varies depending on the population, study, and surgical approach, and patients may experience severe recurrence of postoperative urinary tract infection. Therefore, great attention should be paid to actively intervene to minimize the occurrence of urination and urination [ 27 , 28 ]. The results of this study showed that the incidence of urinary incontinence and voiding was 4% (2 cases) in the study group and 18% (9 cases) in the study group.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Recently, semi-quantitative approaches using standardised forms (e.g. estimation tables) have been employed to quantify micromorphological constituents, thereby enabling the comparison of microfacies (Brönnimann et al, 2020;Lo Russo et al, 2022). Nevertheless, expert analysis can be subjective, and the standardisation of micromorphological descriptions is still low (Stoops, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The soil sample was taken in the central aisle where layers resulting from occupation, destruction and construction activities are present. Ash residues were only observed in low concentration in the thin section, as they probably dissolved through taphonomic processes (ongoing study; see also Lo Russo 2021, Lo Russo et al 2022. The coin was lying in a charcoal rich deposit between ample bone fragments and few mortar residues.…”
Section: The Coinsmentioning
confidence: 97%
“…However, newer studies show a probable complex use of the central aisle, where e.g. charcoal and burnt bones seem to have been spread on the floor (Lo Russo et al 2022). In modern times a lime slaking pit was installed on top of the Roman structure and the area was used as vine yard.…”
Section: The Coinsmentioning
confidence: 99%